Baicalin, a prodrug able to reach the CNS, is a prolyl oligopeptidase inhibitor - Tarragó, Teresa; Kichik, Nessim; Claasen, Birgit; Prades, Roger; Teixidó, Meritxell; Giralt, Ernest (Bioorganic & medicinal chemistry, 2008)
Prolyl oligopeptidase is a cytosolic serine peptidase that hydrolyzes proline-containing peptides at the carboxy terminus of proline residues. It has been associated with schizophrenia, bipolar affective disorder, and related neuropsychiatric disorders and therefore may have important clinical implications. In a previous work, we used 19F NMR to search for new prolyl oligopeptidase inhibitors from a library of traditional Chinese medicine plant extracts, and identified several extracts as powerful inhibitors of this peptidase. Here, the flavonoid baicalin was isolated as the active component of an extract of Scutellaria baicalensis roots having prolyl oligopeptidase inhibitory activity. Baicalin inhibited prolyl oligopeptidase in a dose-dependent manner. Inhibition experiments using baicalin analogs showed that the sugar moiety was not necessary for activity. The IC 50s of baicalin and its aglycone derivative baicalein were rather similar, showing that the sugar moiety was not involved in the interaction of baicalin with POP. These results were confirmed by saturation transfer difference NMR experiments. To further understand the absorption and transport mechanisms of baicalin and baicalein, we evaluated their transport in vitro through the gastrointestinal tract and the blood–brain barrier using a Parallel Artificial Membrane Permeability Assay. The molecule which potentially crosses both barriers was identified as baicalein, the aglycone moiety of baicalin. Our results show that baicalin is a new prodrug able to inhibit prolyl oligopeptidase. As baicalin is a natural compound with a long history of safe administration to humans, it is a highly attractive base from which to develop new treatments for schizophrenia, bipolar affective disorder, and related neuropsychiatric diseases.